Gender discrepancies in predictors for newly onset cardiovascular events and metabolic syndrome in elderly patients from rural China - Yu, Shasha; Guo, Xiaofan; Li, GuangXiao; Yang, Hongmei; Zheng, Liqiang; Sun, Yingxian (Frontiers in Cardiovascular Medicine, 2022)
Objective The study aimed to estimate the possible predictors of cardiovascular events (CVEs) in elderly patients with metabolic syndrome (MetS) from rural China. Moreover, we also attempted to find the potential risk factors for newly diagnosed MetS. Methods The Northeast China Rural Cardiovascular Health Study (NCRCHS) is a community-based prospective cohort study carried out in rural areas of northeast China. Approximately 1,059 elderly patients with MetS but no cardiovascular diseases and 1,565 elderly patients without MetS at baseline were enrolled in this study. They underwent a physical examination, completed a questionnaire in 2012–2013, and were followed up during 2015–2017. Cox proportional hazard analysis was conducted to assess the possible predictors of newly developed CVEs, and multivariate analysis was used to estimate the risk factors of newly diagnosed MetS. Results The common predictors of newly developed CVEs in both men and women were family history of stroke (HR [hazard ratios] female: 1.696; HR male: 2.504) and soybean consumption (HR female: 0.253; HR male: 0.130). Moreover, minority race (HR: 0.109), systolic blood pressure (SBP) (HR: 1.021), current drinking habits (HR: 2.551), family history of hypertension (HR: 2.297), LDL-C (HR: 1.669), 5,000–20,000 CNY/year annual income (HR: 0.290), and strenuous physical activity (HR: 0.397) were predictors of CVEs only in male elderly patients. For newly diagnosed MetS, body mass index (OR female: 1.212; OR male: 1.207) and fasting blood glucose (OR female: 1.305; OR male: 1.217) were common risk factors in both genders, whereas age (OR:0.958) was a protective factor in men and > 9-h/day sleep duration (OR:0.212) was a protective factor in women. In addition, SBP (OR:1.014) ≥4 times/day, bean consumption (OR:1.955), and uric acid (OR:1.005) increased the risk of MetS in men but not in women. Conclusion Our study identified many effective predictors of CVEs in rural elderly patients with MetS and confirmed the presence of a gender-based discrepancy. Moreover, we also identified additional risk factors, along with the traditional ones, for newly diagnosed MetS in rural elderly patients.